2003
DOI: 10.1076/jcen.25.4.465.13875
|View full text |Cite
|
Sign up to set email alerts
|

Using the WMS-III Faces Subtest to Detect Malingered Memory Impairment

Abstract: The current study evaluated the utility of the WMS-III Faces I subtest (Faces) for the assessment of malingering. Thirty nonlitigating traumatic brain injury patients and 30 control participants were administered Faces under standard administration and instructed malingering conditions. Although the two groups obtained similar scores when taking the test under standard instructions, both groups produced significantly lower performances when instructed to malinger, indicating that Faces is sensitive to malinger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 46 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…Thus, it is important to study effects of coaching on different single or combined measures used to detect feigned memory performance. In previous research employing analog designs, healthy participants were instructed to feign memory impairment and were provided with different amounts of information on the sequelae of brain injury and on the procedures involved in neuropsychological testing (for notable exceptions including a group of brain-injured patients, see [ 27 , 28 ]). For most of the studied measures, naïve malingerers and malingerers who received information about the most common symptoms of brain injury (symptom coached simulators) were relatively easy to detect.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important to study effects of coaching on different single or combined measures used to detect feigned memory performance. In previous research employing analog designs, healthy participants were instructed to feign memory impairment and were provided with different amounts of information on the sequelae of brain injury and on the procedures involved in neuropsychological testing (for notable exceptions including a group of brain-injured patients, see [ 27 , 28 ]). For most of the studied measures, naïve malingerers and malingerers who received information about the most common symptoms of brain injury (symptom coached simulators) were relatively easy to detect.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is quite possible that, because of the small sample size of stimuli used in the MAS (n = 10) and RBMT (n = 5), these subtests may not be sensitive enough to detect deficits in facial memory. The exception is the WMS-III Faces subtest, which has begun to receive attention in the recent literature; findings have suggested that this test is sensitive to deficits in autism, temporal lobectomy, and possibly to malingered neurocognitive deficits (Doss, Chelune, & Naugle, 2004;Glassmire et al, 2003).…”
mentioning
confidence: 98%
“…This is a critical issue. Over the past several years, researchers have been encouraging the use of Bayesian methods (eg, 20,21 ) for effort testing (eg, 11,22–28 ). Unfortunately, Bayesian methods, and other interesting statistical methodologies (eg, 29,30 ), including odds and likelihood ratios (eg, 31–34 ), are rarely used in mainstream clinical practice.…”
Section: Test Of Memory Malingering (Tomm) Trial 2 Performances In CLmentioning
confidence: 99%